Стародубское ополье в IX—XII вв. - Гурьянов, В.Н.; Шинаков, Е.А. (Археологія, 1998)
В работе на основе археологического материала и привлечения данных физической географии рассматривается процесс заселения одного из микрорегионов Древней Руси в ІХ—ХІІ вв. Стародубське опілля є унікальним регіоном в плані фізико-географічних характеристик та політико-географічного положення. Слабозаселене раніше балтами Стародубське опілля у процесі заселення слов’янськими племенами у IX ст. опинилось між двома колонізаційними потоками — сіверян та радимичів, які з різних причин наприкінці IX — першій половині X ст. зачепили лише його околиці (І етап слов’янського заселення опілля). Водночас у зв’язку з функціонуванням шляху «великого полюддя» на околицях опілля виникли і перші становища русів, з’явилися скарби.
Другий період освоєння опілля (друга половина X — середина XI ст. тісно пов’язаний з процесом «державного освоєння» Києвом земель Подесення, для якого цей мікрорегіон слугував основною військовою базою. Фіксується приплив різноплемінного населення (поляни, скандинави, фіни, кривичі), яке концентрувалося у великих (понад 10 га) поселеннях типу с. Левенки. До цього періоду належать всі камерні поховання опілля, виникнення основної частини укріплених поселень. Розпочалося інтенсивне сільськогосподарське освоєння родючих (темно-сірих лісових та черноземоподібних) грунтів, підтримане державою.
Повне у демографічно-господарському плані заселення опілля, внутрішнє, аж до маленьких селищ на найдрібніших струмках, освоєння його земель припадає на третій період (кінець XI — XII ст.). Опілля (в основному в природних кордонах) стає, можливо, ключовою волостю з кількома містами та володарськими поселеннями на порубіжжі Чернігівського, Новгород-Сіверського та Смоленського князівств, переживаючи у цю добу економічний розквіт і стоячи на порозі зміни своєї екосистеми під впливом антропогенного фактору. У статті наводиться практично повна сучасна історіографія вивчення давньоруського періоду в Історії Стародубського опілля. The Starodubian opolie is a unique territory in the physicogeographical aspect and as to the politico-geographical position. In the process of population of the Desna River banks by Slavonic tribes the Starodubian opolie, which previously was slightly populated by the Balts, in the 9th century had found itself between two colonization flows: the severyans and the radimichi. In view of different reasons (a demographic reason for the severyans and an economic reason — soils of opolie were unusable for cutting-fire agriculture — for the radimichi) those tribes populated only environs of that region at the end of the 9th and the first half of the 10th century (the 1st stage of the sllavonic population of opolie). At that very time the first sites of the Ruses and treasures appeared in the environs of opolie as a result of functioning of the way «great polyudie» (the way for many people).
The second period of the opolie assimilation (the second half of the 10th and the mid of the 11th century) is tightly connected with the process of «statehood assimilation» of the Desna River territories by Kiev for which that region served the main military base. Various tribes concentrate in large (over 10 hectares) settlements near Levenki and Ryabtsevo: Polyane, Scandinavians, Finns, Krivichi. All chamber graves of opolie and the appearance of fortified settlements belong to this period. Intensive agricultural development of dark-grey and chernozem soils begins. The state promotes the population of the region.
The complete internal demographic-economic population of opolie, small sites on brooks included, development of the lands takes place in the third period (end of the 11th and 12th century). Opolie in its natural boundaries has become, probably, a key region with several towns and landlord settlements on the border of the Chernigov, Novgorod-Seversky and Smolensk principalities. In that epoch, it suffered the prime of its economy and was on the eve of modification of its ecosystem under the effect of anthropogenic factors. The paper presents an almost complete updated historiography of the old Russian period in the history of Starodubian opolie.